Systematic Review of the Literature About the Effects of the COVID-19 Pandemic on the Lives of School Children - Cachón-Zagalaz, Javier; Sánchez-Zafra, María; Sanabrias-Moreno, Déborah; González-Valero, Gabriel; Lara-Sánchez, Amador J.; Zagalaz-Sánchez, María Luisa (Frontiers in Psychology, 2020)
Background: The year 2020 has been marked by the emergence of COVID-19, this virus has reached many countries and has paralysed the lives of many people who have been forced to stay at home in confinement. There have been numerous studies that have sought to analyze the impact of this pandemic from different perspectives, however, this study will pay attention to how it has affected and how it may affect children between 0 and 12 years in the future after the closure of schools for months. Objective: The objective of this article is to learn about the research carried out on the child population in times of confinement, especially those dealing with psychological and motor aspects of minors. Methods: To carry out this systematic review, the PRISMA statement has been followed to achieve an adequate and organized structure of the manuscript. The bibliography has been searched in the WOS, SCOPUS and DIALNET databases, using as keywords: "COVID-19" and "Children". The criteria that were established for the selection of the articles were (1) articles focusing on an age of up to 12 years; (2) papers relating COVID-19 to children; (3) studies analysing the psychological and motor characteristics of children during confinement Results: A total of 9 manuscripts related to psychological and motor factors in children under 12 have been found. The table presenting the results includes the authors, title, place of publication and key ideas of the selected manuscripts. Conclusion: After concluding the systematic review, it has been detected that there are few studies that have focused attention on the psychological, motor or academic problems that can lead to minors after a situation of these characteristics. Similarly, a small number of studies have been found that promote actions at the family and school level to reverse this situation when life returns to normal. These results may be useful for future studies that seek to expand the information according to the evolution of the pandemic.